2019
DOI: 10.1111/birt.12448
|View full text |Cite
|
Sign up to set email alerts
|

The role of the respectful maternity care model in São Paulo, Brazil: A cross‐sectional study

Abstract: Introduction The promotion of a positive birth experience has been a main goal of the World Health Organization’s (WHO) recent work on improving maternity care. The purpose of this study was to assess the cesarean rates, the prevalence of birth practices, perinatal outcomes, and maternal satisfaction, in women involved with the respectful maternity care (RMC) support groups in Sao Paulo, Brazil. Methods This was a cross‐sectional study of women with low‐risk pregnancies who were assisted by professionals recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Doctors/nurses/midwives provide to women in labor and birth (to strengthen their capabilities): a. Pharmacological and b. Non-pharmacological pain relief options and supportive care Reis et al [ 36 ]; International Federation of Gynecology and Obstetrics and others. [ 27 ]; Rosen et al [ 37 ]; Thompson et al [ 38 ]; Warren [ 15 ]; Miller et al [ 39 ]; Sheferaw et al [ 40 ]; Sheferaw [ 41 ] ; World Health Organization [ 22 ]; Kujawski [ 42 ]; Oosthuizen [ 43 ]; Asefa [ 44 ]; Bohren [ 45 ]; Dynes [ 46 ]; Shakibazadeh [ 47 ]; Taavoni [ 48 ]; Wassihun [ 49 ]; World Health Organization [ 50 ]; Afulani [ 51 , 52 ]; Giordano [ 53 ]; Oliveira [ 54 ]; Perkins [ 55 ]; Afulani [ 56 ]; Bante [ 57 ]; Bohren [ 58 ]; Butler [ 59 ]; Lothian [ 24 ]; Montoya [ 60 ]; Moridi [ 61 ]; Devries [ 62 ] Page [ 63 ] Wagner [ 64 ] GarciadeLimaParada [ 65 ] Behruzi [ 66 ] Behruzi [ 67 ] Behruzi [ 68 ] Binfa [ 69 ] Ouedraogo [ 70 ] ConesaFerrer [ 71 ] Binfa [ …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doctors/nurses/midwives provide to women in labor and birth (to strengthen their capabilities): a. Pharmacological and b. Non-pharmacological pain relief options and supportive care Reis et al [ 36 ]; International Federation of Gynecology and Obstetrics and others. [ 27 ]; Rosen et al [ 37 ]; Thompson et al [ 38 ]; Warren [ 15 ]; Miller et al [ 39 ]; Sheferaw et al [ 40 ]; Sheferaw [ 41 ] ; World Health Organization [ 22 ]; Kujawski [ 42 ]; Oosthuizen [ 43 ]; Asefa [ 44 ]; Bohren [ 45 ]; Dynes [ 46 ]; Shakibazadeh [ 47 ]; Taavoni [ 48 ]; Wassihun [ 49 ]; World Health Organization [ 50 ]; Afulani [ 51 , 52 ]; Giordano [ 53 ]; Oliveira [ 54 ]; Perkins [ 55 ]; Afulani [ 56 ]; Bante [ 57 ]; Bohren [ 58 ]; Butler [ 59 ]; Lothian [ 24 ]; Montoya [ 60 ]; Moridi [ 61 ]; Devries [ 62 ] Page [ 63 ] Wagner [ 64 ] GarciadeLimaParada [ 65 ] Behruzi [ 66 ] Behruzi [ 67 ] Behruzi [ 68 ] Binfa [ 69 ] Ouedraogo [ 70 ] ConesaFerrer [ 71 ] Binfa [ …”
Section: Resultsmentioning
confidence: 99%
“…Provide honest and complete information, b .Involve clients in decision making about their care, c. Solicit consent for all interventions, and d. Respect choices including refusal of interventions Reis et al [ 36 ]; Warren et al [ 73 ]; International Federation of Gynecology and Obstetrics and others. [ 27 ]; Rosen et al [ 37 ]; Thompson et al [ 38 ]; Warren [ 15 ]; Miller et al [ 39 ]; Patel et al [ 74 ]; Sheferaw et al [ 40 ]; Solnes et al [ 75 ]; World Health Organization [ 22 ]; Kambala [ 76 ]; Kujawski [ 42 ]; Ndwiga [ 77 ]; Oosthuizen [ 43 ]; Sheferaw [ 41 ]; Vedam et al [ 78 , 79 ]; Asefa [ 44 ]; Bohren [ 45 ]; Dynes [ 46 ]; Shakibazadeh [ 47 ]; Taavoni [ 48 ]; World Health Organization [ 50 ]; Afulani [ 51 , 52 , 80 ]; Feijen-deJong [ 81 ]; Giordano [ 53 ]; Perkins [ 55 ]; Afulani [ 56 ]; Ayoubi [ 82 ]; Bohren [ 58 ]; Butler [ 59 ]; Lothian [ 24 ]; Moridi [ 61 ]; Montoya [ 60 ]; Page [ 63 ] Wagner [ 64 ] Guimaraes [ 84 ] GarciadeLimaParada [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Consistent with other studies on the effect of companionship during labor on intrapartum care, companionship during labor facilitates spontaneous vaginal delivery and reduces the intensity of pain 27 and maternal satisfaction. 28 Given the global epidemic of unnecessary cesarean birth, increasing coverage of nonclinical interventions such as companionship during labor can reduce the risk of unnecessary cesarean births. 29,30 In low-income families, providing support during labor may be more difficult as family members working on a daily wage basis may lose the household income.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of maternal as well as neonatal and infant mortality and morbidity is associated with disrespectful maternity care in LMICs [4]. Existence of RMC has good short-term and long-term outcomes on the mother and her family [8]. A review by Shakibazadeh et al, in 2018 have concluded that the concept of RMC is broader than just reduction of disrespectful care or minimising mistreatment of women during childbirth [9].…”
Section: Introductionmentioning
confidence: 99%